Measures of Counteracting Domestic Violence Committed by Children: Problematic Aspects - A. S. Bakhaieva (Bulletin of Kharkiv National University of Internal Affairs)
The problem of domestic violence is quite urgent in our country. Domestic violence is a heavy burden both for the victim and for society in the whole. Typically, the most vulnerable family members who suffer from domestic violence are women, children and the elderly, and the perpetrators are most often men. But a child can also commit domestic violence, as evidenced by the legal definition of the term of “a child- abuser”. However, this phenomenon is insufficiently studied and is rarely discussed by Ukrainian scholars.